2022
DOI: 10.1038/s41467-022-28310-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome of the largest living rodent harbors unprecedented enzymatic systems to degrade plant polysaccharides

Abstract: The largest living rodent, capybara, can efficiently depolymerize and utilize lignocellulosic biomass through microbial symbiotic mechanisms yet elusive. Herein, we elucidate the microbial community composition, enzymatic systems and metabolic pathways involved in the conversion of dietary fibers into short-chain fatty acids, a main energy source for the host. In this microbiota, the unconventional enzymatic machinery from Fibrobacteres seems to drive cellulose degradation, whereas a diverse set of carbohydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 91 publications
2
21
0
Order By: Relevance
“…Carbohydrate fermentation is a critical function of the human gut microbiota, and then the fermented carbohydrates produce important metabolites in gut, such as short-chain fatty acids (SCFAs), and succinate ( Canfora et al, 2019 ). Mechanistically, the gut microbiome harbors distinct enzymatic systems, including a glycoside hydrolase family of β-galactosidases and a carbohydrate-binding module family, to degrade plant-derived polysaccharides ( Cabral et al, 2022 ). These processes are essential to maintain gut microbiota that depends mostly on non-digestively polysaccharides and fibers as energy sources ( Sonnenburg and Sonnenburg, 2014 ).…”
Section: Supplementation Of Natural Polysaccharides Ameliorate Hfd-in...mentioning
confidence: 99%
“…Carbohydrate fermentation is a critical function of the human gut microbiota, and then the fermented carbohydrates produce important metabolites in gut, such as short-chain fatty acids (SCFAs), and succinate ( Canfora et al, 2019 ). Mechanistically, the gut microbiome harbors distinct enzymatic systems, including a glycoside hydrolase family of β-galactosidases and a carbohydrate-binding module family, to degrade plant-derived polysaccharides ( Cabral et al, 2022 ). These processes are essential to maintain gut microbiota that depends mostly on non-digestively polysaccharides and fibers as energy sources ( Sonnenburg and Sonnenburg, 2014 ).…”
Section: Supplementation Of Natural Polysaccharides Ameliorate Hfd-in...mentioning
confidence: 99%
“…In captive sifakas (Propithecus coquereli), supplementing standard diets with diverse foliage blends versus with single plant species, was associated with greater concentrations of short-chain fatty acids (SCFAs) in the gut (123). At a larger scale across wild mammals, from rodents to carnivores and primates, several studies have found associations between specific microbial functions and diet type (herbivore, omnivore, piscivore, carnivore) (35,124,125).…”
Section: Host Diet Is Correlated With Gut Microbiome Variationmentioning
confidence: 99%
“…Buffalo Metagenomic analysis of the rumen showed presence of Bacteroidetes, Spirochaete and an unidentified bacterial phylum (Bohra et al, 2022;Cabral et al, 2022) Frontiers in Chemical Engineering frontiersin.org genera are Pseudomonas, Staphylococcus, Enterobacter, Aeromonas, etc. (Siddiqui et al, 2022), while there is little information on the gut microbiome of amphibians.…”
Section: An Et Al (2020)mentioning
confidence: 99%